Management of Waqf Land in Tanjung Morawa District According to Law Number 41 of 2004 (Analysis of Nazir Performance in Productive Waqf Development) - Iqbal, Muhammad Nur; Arfa, Faisar Ananda; Irham, M. Iqbal (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The purpose of the research is to find out how the performance of Nazhir in the management of waqf land in Tanjung Morawa Subdistrict, to find out what are the steps taken by Nazhir in Tanjung Morawa Subdistrict in productive waqf management, and to find out what are the inhibiting factors for productive waqf management in Tanjung Morawa Subdistrict. The research conducted is social research. The research method used in this discussion is qualitative research method. The approach that the author uses in discussing this research is an empirical or sociological approach. The method of data collection carried out by the author is by means of field observation and examining the data sources that the author mentions, namely primary, secondary, and tertiary. The management of waqf land carried out by Nazhir in Tanjung Morawa District has not led to productive waqf, only limited to maintenance and utilization, In general, the management of waqf land in Tanjung Morawa District is still in the traditional and consumptive period, which is only effective in terms of social religion. The steps taken by Nazhir in developing waqf productively in Tanjung Morawa District are: The making of the baitul Mall box carried out by the Nazhir of the Shalatul falah mosque and the management of rice fields as a baitul mall carried out by Mr. Masduki in Punden Rejo Village, where the proceeds from the rice fields are used as a source of KAS income for the mosque and are also distributed to underprivileged people. factors that hinder the development of productive waqf in Tanjung Morawa District, including: The strength of the old understanding of Muslims regarding waqf management, Lack of socialization to Nazir and Nazirs who are not professional in carrying out productive waqf management.